Spatially explicit assessment of water stress and potential mitigating solutions in a large water-limited basin: the Yellow River basin in China - W. Zhang; W. Zhang; X. Zhao; X. Zhao; X. Gao; W. Liang; J. Li; B. Zhang (Hydrology and Earth System Sciences)
Comprehensive assessment of the long-term evolution of water stress and its driving factors is essential for designing effective water resource management strategies. However, the roles of water withdrawal and water availability components in determining water stress and potential mitigating measures in large water-scarce basins are poorly understood. Here, an integrated analytical framework was applied to the Yellow River basin (YRB), where the water crisis has been a core issue for sustainable development. The analysis suggests that the YRB has experienced unfavorable changes in critical water stress indicators over the past 56 years. Compared to the period from 1965 to 1980, the regional water stress index (WSI) and the frequency and duration of water scarcity increased by 76 %, 100 %, and 92 %, respectively, over the most recent 2 decades. Water withdrawal was the primary driver of the increased WSI before 2000; however, it has since contributed as much as water availability. Meanwhile, local water management and climate change adaptation were shown to be important in determining total water availability at the sub-basin scale. Water demand in the 2030s is predicted to be 6.5 % higher than during 2001–2020 (34.2 km3) based on the trajectory of historical irrigation water use and corrected socio-economic data under different Shared Socioeconomic Pathways (SSPs). To meet all sectoral water needs, a surface water deficit of 8.36 km3 is projected. Potential improvements in irrigation efficiency could address 25 % of this deficit, thereby alleviating the pressure on external water transfer projects. Such efficiency gains would enable the WSI of the YRB in the 2030s to be maintained at the current level (0.95), which would worsen conditions for 44.9 % of the total population while easing them for 10.7 % compared to in the 2000s. Our results have vital implications for water resource management in basins facing similar water crises to that in the YRB.